Integrating The Features Of Knowledge Management (KM) And Business Intelligence (BI) For Developing Organizational Performance Framework-A Diagnostics Dashboard - Jayakrishnan, Mailasan; Mohamad, Abdul Karim; Mohd Yusof, Mokhtar (American Scientific Publishers, 2018)
This paper will explain specific features of Knowledge Management (KM) and Business Intelligence (BI) in viewing the big picture of their decision-making processes when implementing organizational performance diagnostics framework. In today’s digital era, KM and BI are two important model and techniques in enabling organizations toward deriving better intelligence knowledge-level creation and decision making. By structuring and using KM and BI together as a key performance of organizational operations for adapting and dealing with problematic-scenarios like data deluge. This paper focuses upon visualizing the organizational analytics ability for strategic performance decisions. Therefore, this conceptual framework relates the current KM and BI stages in strategy implementation for displaying an organizational performance indicator. The research goal is to provide a comprehensive understanding of emerging knowledge from structuring KM and BI stages and their mashup characteristics in designing the organizational performance framework. The outcome will be a design of a typical strategic performance application – the organizational diagnostics dashboard.